Titel prent: Bevredig de nieuwsgierigheid : "De morgenpost was er nieuwsgierig naar wie het eind van de strop zou pakken..." - Hahn, Albert
Titel prent: Bevredig de nieuwsgierigheid : "De morgenpost was er nieuwsgierig naar wie het eind van de strop zou pakken...".